Новый вид цестод врановых птиц — Satyolepis skrjabini sp. n. (Hymenolepididae) - Чернобай, В.Ф. (Вестник зоологии, 1969)
In Corvidae of Volgograd region a new species was found Cestodes Satyoelepis skrjabini, which is characterized by the presence of 16 hooks of «diorchis» type, length 0.028=0.030 mm. Three oval testicles are arranged according to type VII. Cirrus of 0.095 x 0.006 mm size has small thorns. Cirrus ponch is flack-like, its size — 0.120=0.125X X0.99 mm. Eggs are round 0.072=0.080 mm. Length of embryonal hooks of the side pail — 0.023=0.024 mm, middle pair — 0.026 mm.